Design and synthesis of new lupeol derivatives and their α-glucosidase inhibitory and cytotoxic activities. Issue 1 (22nd December 2021) - Phan, Hoang-Vinh-Truong; Duong, Thuc-Huy; Pham, Duc-Dung; Pham, Hoang-Anh; Nguyen, Van-Kieu; Nguyen, Thi-Phuong; Nguyen, Huu-Hung; Nguyen, Ngoc-Hong; Sam-ang, Pornpat; Phontree, Kiettipum; Sichaem, Jirapast
Abstract: A series of lupeol derivatives 2, 2a-2f, 2a-2h, 3a-3e, and 4a-4b were designed, synthesised and evaluated for their α -glucosidase inhibitory and cytotoxic activities. Among synthetic derivatives, lupeol analogues 2b and 2e containing a benzylidene chain exhibited the best activity against α -glucosidase and superior to the positive agent with the IC50 values of 29.4 ± 1.33 and 20.1 ± 0.91 μM, respectively. Lupeol analogues 2d and 3a showed weak cytotoxicity against K562 cell line with the IC50 values of 76.6 ± 2.40 and 94.4 ± 1.51 μM, respectively. Graphical Abstract: